2019
DOI: 10.5125/jkaoms.2019.45.5.254
|View full text |Cite
|
Sign up to set email alerts
|

Surgical extrusion of a maxillary premolar after orthodontic extrusion: a retrospective study

Abstract: ObjectivesCrown-root fracture and cervical caries in maxillary premolars constitute a challenge in cases of subgingival placement of restoration margins. Surgical extrusion has been practiced successfully in permanent anterior teeth. The aim of the present retrospective study was to assess the clinical outcome of surgical extrusion after orthodontic extrusion in maxillary premolars.Materials and MethodsTwenty-one single, tapered root maxillary premolars with subgingival crown-root fracture or caries were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…To overcome this problem, in 2010, a new protocol called "Atraumatic Safe Extraction" (ASE) was introduced by Choi et al, whereby a preoperative orthodontic extrusion for 2-3 weeks is performed before surgery to increase the mobility and volume of the periodontal ligament of the tooth to be intentionally replanted [1,82,83]. The preoperative orthodontic mobilization makes extraction easier, thus reducing the risk of complications such as root resorption and ankylosis [82,83].…”
Section: Combined Therapymentioning
confidence: 99%
See 4 more Smart Citations
“…To overcome this problem, in 2010, a new protocol called "Atraumatic Safe Extraction" (ASE) was introduced by Choi et al, whereby a preoperative orthodontic extrusion for 2-3 weeks is performed before surgery to increase the mobility and volume of the periodontal ligament of the tooth to be intentionally replanted [1,82,83]. The preoperative orthodontic mobilization makes extraction easier, thus reducing the risk of complications such as root resorption and ankylosis [82,83].…”
Section: Combined Therapymentioning
confidence: 99%
“…The author suggested that performing a preoperative orthodontic extrusion would increase the volume of the periodontal ligament of the donor tooth, preventing root resorption after transplantation [83,85]. In the ASE protocol, the same concept was adapted as that of intentional replantation to prevent root resorption [1,83]. Similarly, the same methodology should be applied to surgical extrusion techniques as well; its use has been described only in a retrospective study by Choi et al in 2019 [1].…”
Section: Combined Therapymentioning
confidence: 99%
See 3 more Smart Citations